Condition of pro-oxidant and antioxidant systems in guinea pigs' lungs under the condition of immobilization stress - Mykhailo Stepanovych Reheda; Marta Yevhenivna Kovalska; Mariana Ljubomurivna Baida (Kazimierz Wielki University, 2017)
We have investigated the results of alterations in indices of pro-oxidant (conjugated diene and malondialdehyde ) and antioxidant (superoxide dismutase, ceruloplasmin, catalase) systems in guinea pigs' lungs  under the conditions of immobilization stress. The experiment was conducted on 40 female guinea pigs weighing 0.18-0.20 kg. The animals were divided into 4 groups, each contained 10 guinea pigs: I - intact guinea pigs ( control), II-guinea pigs with model of IS on1st day of experiment;Ш-animals on 2nd  day of experiment;IV- group of animals on 34th day of experimental model of IS. The results of our experimental work showed  a significant accumulation of lipid peroxidation products in the lung`s tissure in different periods ( on 1st, 2nd and 34th days) of immobilization stress. The state of antioxidant defence was characterized by moderate decrease of inzymes activity (superoxide dismutase, catalase and ceruloplasmin). disorders of balance between pro-oxidant and antioxidant systems couse oxidative stress development.